De‐escalating medical therapy in Crohn's disease patients who are in deep remission: A RAND appropriateness panel. Issue 3 (29th May 2019) - Sparrow, Miles P.; Melmed, Gil Y.; Devlin, Shane; Kozuch, Patricia; Raffals, Laura; Loftus Jr, Edward V.; Rubin, David T.; Spiegel, Brennan; Baidoo, Leonard; Bressler, Brian; Cheifetz, Adam; Irving, Peter; et al.
Summary: Background: Deep remission is a treatment goal for patients with Crohn's disease, after which de‐escalation of medical therapy may be considered. However, applicability of available study data to real‐world clinical practice can be challenging. Aim: We evaluated the appropriateness of de‐escalating immunomodulator or anti‐tumour necrosis factor therapy in Crohn's disease patients in deep remission. Methods: A literature review was presented to a panel of international experts in Crohn's disease. Appropriateness of de‐escalation in patients in deep remission for at least 6 months was considered in 240 scenarios across five chapters. Using a modified Delphi method, panel members rated appropriateness of de‐escalation in each scenario via a web‐based survey, then met to discuss the topic and re‐rated the scenarios. Scenarios with disagreement were rated as uncertain. Results: De‐escalation was rated appropriate in only 32/240 scenarios (13.3%), including 19 of elderly patients on combination therapy. De‐escalation was rated inappropriate in 59/240 scenarios (24.6%), including 22 of patients on monotherapy and 35 of patients on combination therapy stopping anti‐tumour necrosis factor therapy. More than 60% of scenarios (149/240) were rated uncertain, including 42 of patients with complicated disease on combination therapy stopping or dose‐reducing immunomodulators. Conclusions: Discontinuing anti‐tumour necrosis factor or immunomodulator therapy was largely not recommended, except in scenarios of elderly patients with uncomplicated CD or those on combination therapy stopping or dose‐reducing immunomodulators. As nearly two‐thirds of scenarios were rated uncertain, additional data are needed to better inform clinicians regarding the benefits and risks of de‐escalating medical therapy in Crohn's disease.